Photodegradation of azo‐dyes in aqueous solution by polyacrylonitrile nanofiber mat‐supported metalloporphyrins. Issue 2 (22nd June 2012) - Shao, Linjun; Xing, Guiying; Lv, Weixi; Yu, Huijun; Qiu, Mingxi; Zhang, Xian‐Man; Qi, Chenze
Abstract Electrospinning has been employed to fabricate uniform polyacrylonitrile and polyacrylonitrile copolymer nanofiber mats supporting metalloporphyrins (MTPP; M: Zn(II), Cu(II), Ni(II), Co(II), Fe(III) and Pd(II); TPP: meso‐tetraphenylporphyrin). The nanofiber mat‐supported metalloporphyrins are shown as efficient photocatalysts for the degradation of various azo‐dyes in aqueous solutions under visible light irradiation. The effect of transition metals on azo‐dye photodegradation has been examined. The nanofiber mat‐supported copper–porphyrin and iron–porphyrin complexes are among the most effective photocatalysts for azo‐dye degradation. Immobilization of the metalloporphyrins onto the nanofiber mats greatly facilitates the recovery and reuse of the expensive and toxic photocatalysts. Most interestingly, there are no significant degradations of the photocatalytic activities of the recycled photocatalysts. © 2012 Society of Chemical Industry